(untitled) (Development Service Industry Management, 2024)
Modern scientific developments on the issues of staff evaluation in the field of services and, in particular, veterinary medicine services are considered. Since veterinary activity is not only services for the prevention, diagnosis and treatment of animal diseases, but also work to prevent their transmission to humans, consulting and breeding activities, work in the direction of preserving the health and productivity of animals, implementation of vaccination programs, etc., the question of evaluation personnel in this field is extremely important not only in the context of achieving the goals of a certain economic entity, but also in the context of ensuring the protection of animals and the population of certain territories from the spread of diseases, promoting the growth of the population’s awareness of the organization of proper care and prevention of animal diseases, then the issues of effective evaluation of the staff of veterinary institutions become of special importance. The purpose of the study is to substantiate the peculiarities of the assessment of the medical staff of veterinary institutions in the context of ensuring that they provide effective and high-quality services. In the course of achieving the set goal, general scientific and special methods of scientific research were applied, and, in particular, methods of abstraction, theoretical generalization, grouping, logical analysis and synthesis. The basic models of evaluation of veterinary workers and the composition of their key competencies were studied. The areas of responsibility of the owners of veterinary institutions for the level of competence of their medical personnel, which must be taken into account in personnel evaluation methods, are substantiated. Ways of developing the methodology for evaluating the medical staff of veterinary institutions and a list of possible directions and evaluation indicators are proposed, the application of which will make it possible to evaluate not only the level of competence and the effectiveness of the work of each individual employee, but also the effectiveness of team interaction and the role of each individual in the results of teamw.